Effect of Mass and Adsorption Time of Methylene Blue Dyes Using Green Shell Chitosan as Adsorbent - Maulana, Moh Ridho; Mustakim, Zainal (Side: Scientific Development Journal, 2024)
In this research, methylene blue was reduced using waste from green kerrang shells. Optimum results for variations in mass and time with masses of 0.1, 0.2, 0.3 grams and 0.1 mg/L methylene blue occurred at a mass of 0.3 grams with 60 minutes. Result of adsorption capacity. Optimum adsorption capacity for Methylene Blue with adsorbent from green mussel shell chitosan with a contact time of 10-60 minutes with variations in optimum adsorption time with a time of 10-60 minutes and a mass of 0.3 grams with an adsorption capacity of 3 mg/ g, From the results of this research, the mass of chitosan has an effect on decreasing the adsorption concentration, which is greater as the contact time increases. In this study, the largest adsorption capacity occurred at a mass of 0.3 grams. In this study, the maximum adsorption removal percentage in the mass variation was at 60 minutes, which means that at 10-50 minutes, the adsorption removal percentage was still gradually increasing with the highest result at 60 minutes with 98.9%.